Declining Literacy Interest in the Era of Disruption: A Qualitative Study on the Influence of Digital Media on Public Reading Habits: Menurunnya Minat Literasi di Era Disrupsi: Studi Kualitatif tentang Pengaruh Media Digital terhadap Kebiasaan Membaca Masyarakat - Sari, Endah Meilani; Ramadhani, Nadhifah Keisha; Jannah, Dian Rokhikhatul; Nabil, Abid Ainun (Medpro, 2024)
The era of digital disruption is characterized by easy access to information through various visual platforms such as social media, short videos, and audio content. While this phenomenon has brought significant changes in how people acquire information, it simultaneously presents new challenges to the interest in and habit of in-depth reading. This study aims to identify the factors contributing to the decline in literacy interest amidst the dominance of digital technology and to formulate strategies that can re-foster a culture of literacy. This research employs a qualitative approach with a case study design. Data collection techniques include non-participant observation and systematic recording of public reading behaviors in daily life. The findings indicate that people tend to prefer consuming instant information via visual and audio media, with a propensity for skimming and a decreased interest in longer texts such as books or academic articles. These findings highlight the need for new literacy approaches that are adaptive to digital formats yet still cultivate deep comprehension. This research contributes to the development of more inclusive, interactive, and media-based digital literacy strategies relevant to modern societal habits.